Broad‐scale patterns of geographic avoidance between species emerge in the absence of fine‐scale mechanisms of coexistence. Issue 9 (26th July 2021) - Novella‐Fernandez, Roberto; Juste, Javier; Ibáñez, Carlos; Rebelo, Hugo; Russo, Danilo; Alberdi, Antton; Kiefer, Andreas; Graham, Laura; Paul, Hynek; Doncaster, Charles Patrick; Razgour, Orly
Abstract: Aim: The need to forecast range shifts under future climate change has motivated an increasing interest in better understanding the role of biotic interactions in driving diversity patterns. The contribution of biotic interactions to shaping broad‐scale species distributions is, however, still debated, partly due to the difficulty of detecting their effects. We aim to test whether spatial exclusion between potentially competing species can be detected at the species range scale, and whether this pattern relates to fine‐scale mechanisms of coexistence. Location: Western Palearctic. Methods: We develop and evaluate a measure of geographic avoidance that uses outputs of species distribution models to quantify geographic exclusion patterns expected if interspecific competition affects broad‐scale distributions. We apply the measure to 10 Palearctic bat species belonging to four morphologically similar cryptic groups in which competition is likely to occur. We compare outputs to null models based on pairs of virtual species and to expectations based on ecological similarity and fine‐scale coexistence mechanisms. We project changes in range suitability under climate change taking into account effects of geographic avoidance. Results: Values of geographic avoidance were above null expectations for two cryptic species pairs, suggesting that interspecific competition could have contributed to shaping their broad‐scale distributions. These two pairs showed highest levels of ecological similarity and no trophic or habitat partitioning. Considering the role of competition modified predictions of future range suitability. Main conclusions: Our results support the role of interspecific competition in limiting the geographic ranges of morphologically similar species in the absence of fine‐scale mechanisms of coexistence. This study highlights the importance of incorporating biotic interactions into predictive models of range shifts under climate change, and the need for further integration of community ecology with species distribution models to understand the role of competition in ecology and biogeography.